2006
DOI: 10.1039/b513179k
|View full text |Cite
|
Sign up to set email alerts
|

Activity of synthetic ion channels is influenced by cation–π interactions with phospholipid headgroups

Abstract: A suite of synthetic hydraphile ion channels has been used to probe the possibility of cation-π interactions between the channel and the phospholipid bilayer. The hydraphiles selected for this study contained either no sidearm, aliphatic sidearms or aromatic sidearms that varied in electron-richness. An ion selective electrode (ISE) method was used to evaluate the ion transport ability of these hydraphiles across synthetic bilayers. Transport was dependent on sidearm identity. Ion transport activity for the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…Compound wGG is positioned so that the DOPA headgroup resides in the cavity known to interact with Cl À in the published study. [40] As noted above (Figure 4), there is no difference in the isotherms observed for WGG and DOPC in the presence or absence of DOPA. This might seem unreasonable considering that DOPA is negatively charged and DOPC is neutral (zwitterionic).…”
Section: Dynamic Light Scattering and Transmission Electron Microscopysupporting
confidence: 55%
See 1 more Smart Citation
“…Compound wGG is positioned so that the DOPA headgroup resides in the cavity known to interact with Cl À in the published study. [40] As noted above (Figure 4), there is no difference in the isotherms observed for WGG and DOPC in the presence or absence of DOPA. This might seem unreasonable considering that DOPA is negatively charged and DOPC is neutral (zwitterionic).…”
Section: Dynamic Light Scattering and Transmission Electron Microscopysupporting
confidence: 55%
“…[39] Third, we have shown that synthetic ion transporters show varying efficacies when cation-p interactions between DOPC and aromatic side chains can occur. [40] These effects are not observed when DOPC is mixed with DOPA, which helps to neutralize the formers ammonium headgroup charge.…”
Section: Dynamic Light Scattering and Transmission Electron Microscopymentioning
confidence: 99%
“…13, the correlation between transport rate and substituent constant is good. The slope (reaction constant ρ) of the line is -0.86 and the correlation coefficient (R 2 ) is also 0.86 [73]. A negative slope is expected for the interaction of a cation with a Lewis basic donor such as tertiary nitrogen.…”
Section: Cation-pi Effects On Transport Efficacymentioning
confidence: 94%
“…The metal ion complexing abilities of crown ethers can be improved significantly by their functionalization with ligating side arms that enhance the cation selectivity and transport through liquid membranes. 3 The C-or N-pivot, bibracchial (two arms) lariat ethers (BiBLEs) 4,5 were modeled on valinomycin complexation and designed to be flexible and dynamic when unbound and enveloping when a guest is complexed. 6 The historically first synthesized N,N 0 -dibenzyl-1,7,10,16-tetraoxo-4,13-diazacyclooctadecane (N,N 0 -dibenzyldiaza-18-crown-6, 2) 4,5,7 has been studied in detail, and it has manifested itself as a good complexing agent for a wide range of metals, both inside the cavity acting in its neutral form and in an outer-sphere coordination.…”
Section: Introductionmentioning
confidence: 99%